ANALISA PENGARUH VISCOSITAS LUMPUR DAN VARIASI DIAMETER PIPA ISAP LUMPUR TERHADAP KAPASITAS ALIRAN PADA MESIN POMPA PENYEDOT LUMPUR - Supardi, Supardi; Julianto, Wawan (Program Studi Teknik Mesin, Universitas 17 Agustus 1945 Surabaya, 2016)
Nowadays, we find several places in towns which hit by floods, it happen because some things, for example water duct which is gagged because of a bunch of rubbish, a small duct just make the water overload, and a shallow duct because of mud sediment. Because of the problem above, there is an idea to design a process to make a simple tool named piping installation on the pump vacuum of mud. This research method is used to analyze the influence of mud viscosity and diameter variation of mud suction pipe to the flow capacity of mud vacuum pump machine. Each of mud viscosity diameter 1,1225 N.s/m², 1,1849 N.s/m². And diameter variable of mud pump vacuum 0,0127m, 0,0191m, 0,0254m. The examiner tries to do this observation in each variable for three times. From the statement above, it can assume that the higher value of mud viscosity the lower of pipeline capacity. In each higher viscosity (η) = 1,3003 N.s/m², in diameter of mud pump vacuum 0,0127m, Qout = 0,0002886 m³/s, in diameter of mud pump vacuum 0,0191m, Qout = 0,0002975 m³/s, in diameter of mud pump vacuum 0,0254m, Qout = 0,0003667 m³/s. Meanwhile, in trial diameter variation of mud suction pipe, the bigger diameter of mud suction pipe the higher of pipeline capacity. So the higher of pipeline capacity is happen in diameter of mud suction pipe 0,0254m with Qout = 0,0003984 m³/s. The higher pipeline viscosity (Qin) is happen in diameter of mud suction pipe 0,0254m which is (Qin) = 0,0001784 m³/s and resulting (Qout) 0,0003984 m³/s.Keywords: Mud pump vacuum, diameter variation of mud suction pipe.